Pengaruh Lapangan Pekerjaan, Daya Beli, Sumber Daya Alam terhadap Kesejahteraan Masyarakat Setelah Adanya Tambang Batubara di Desa Bukit Peranginan - Farhandes Ramadhan; Bambang Kurniawan; M.Taufik Ridho (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to analyze the influence of mining employment, community purchasing power, and the coal sector on community welfare in Bukit Peranginan. Specifically, this study examines: (1) the influence of mining employment on community welfare, (2) the influence of community purchasing power on community welfare, and (3) the influence of the coal sector on community welfare in Bukit Peranginan. This study used a quantitative approach with a survey method. Data collection techniques were conducted through observation, interviews, and questionnaires distributed to community respondents. The data obtained were then analyzed using data quality testing, classical assumption testing, multiple linear regression analysis, coefficient of determination testing, and hypothesis testing to determine the effect of each independent variable on the dependent variable. The results indicate that mining employment does not have a significant influence on community welfare in Bukit Peranginan. Conversely, community purchasing power has been shown to have a significant influence on community welfare. Furthermore, the coal sector also has a significant influence on the level of community welfare in Bukit Peranginan. These findings indicate that improvements in community welfare are more influenced by economic capacity and coal sector activities than by the presence of mining employment itself.